THE EFFECT OF USING WEBBING TECHNIQUE ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABILITY (A Study at the Tenth Grade Students of SMA Negeri 1 Barumun in 2018/2019 Academic Year) - M.Rizki Hidayah Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2020)
the purpose of this research are to find out: 1) The extent is the application of webbing technique in teaching writing descriptive text at the tenth grade students of SMA Negeri1 Barumun, 2) The extent is the students’ writing descriptive text before and after using webbing technique at the tenth grade of SMA Negeri 1 Barumun, 3) Whether there is a significant effect of webbing technique on students’ writing descriptive text of the tenth grade students of SMA N 1 Barumun. The research method is use by experimental method. The population of this research is all of the Tenth Grade Students of SMA Negeri 1 Barumun consist of 306 students and samples are 30 students which taken by purposive sampling and instrument of collecting data use observation sheet and test.The result mean of the application of webbing technique is 3.93 based on the technique of analysis data the criterion of score using webbing technique with categorized “Very Good”. The result students’ writing descriptive text before using webbing technique is 55.50 categorized “Low” while after using webbing technique is 80.76 it was categorized “Good”, to know the result of the data, the research of analysis data use by ttestformula, the result of ttest is 12.07 meanwhile ttable is 2.04, it means that there is a significant effect of webbing technique on students’ writing descriptive text ability at the tenth grade of SMA Negeri 1 Barumun 2018/2019 Academic Years of Ha is accepted